1
$\begingroup$

There is a similar discussion:
Infimal convolution conjugate

I just want to ask how to prove that for convex $f_i$ $\forall i$ if

$$ g(x) = \inf\{f_1(x_1)+f_2(x_2)|x_1+x_2=x\} $$

then $g^{*}(y) = f_1^{*}(y)+f_2^{*}(y)$ ?


We know the definition for the conjugate function is $$g^*(y) = \sup_x \{\langle x,y \rangle - g(x)\} $$

We have the following:
$$g^*(y) = \sup_x \{\langle x,y \rangle - (\inf\{f_1(x_1)+f_2(x_2)|x_1+x_2=x)\} $$

Then how to deal with this complicated term?

$\endgroup$
1
$\begingroup$

Note that $$\begin{align}g^*(y) &= \sup_{x,x_1,x_2} \{ x^Ty - f_1(x_1) - f_2(x_2) | x_1+x_2 = x \} \\ &= \sup_{x_1,x_2} \{ (x_1+x_2)^Ty - f_1(x_1) - f_2(x_2)\} \\ &= \sup_{x_1,x_2} \{ x_1^Ty - f_1(x_1) + x_2^Ty - f_2(x_2)\} \\ &= \sup_{x_1} \{ x_1^Ty - f_1(x_1) \} + \sup_{x_2} \{ x_2^Ty - f_2(x_2)\} \end{align}$$

$\endgroup$
  • $\begingroup$ In the first line, how could you remove the "$\inf$"? ($g(x) = \inf $...) $\endgroup$ – sleeve chen Feb 7 '17 at 9:31
  • 1
    $\begingroup$ I used that $\inf(f(x)) = -\sup(-f(x))$. $\endgroup$ – LinAlg Feb 7 '17 at 9:52
  • $\begingroup$ So from this proof, the identity holds for any proper functions (can be highly discontinuous) defined on any normed vector space that can be infinite dimensional . Right ? $\endgroup$ – Red shoes Jul 1 '17 at 17:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.